Spatial-temporal characteristics and influence factors of high-quality development of animal husbandry industry in China. - Tiantian Su; Cuixia Li (PLoS ONE)
The animal husbandry industry stands as a pillar of the agricultural sector. According to the defining characteristics of high-quality development in animal husbandry, this paper establishes a comprehensive evaluative indicator system. This system evaluates the quality of development in the industry from 2010 to 2022, including five key dimensions: output efficiency, product safety, resource conservation, environmental friendliness, and the level of scientific and technological &management. Results indicate a positive overall trend in the high-quality development of China's animal industry throughout this period. Provinces exhibiting the highest average levels of development are, in descending order, Jiangsu, Shanghai, Anhui, Beijing, Fujian, Yunnan, Chongqing, Gansu, Guangdong, and Guangxi. Among these five dimensions, the level of environmental friendliness and the level of scientific and technological &management are better developed, while the level of resource conservation, the level of product safety, and the level of output efficiency are poorly developed. Regional differences have demonstrated a slight narrowing trend; however, the effect of intra-regional differences on the overall differences has remained relatively stable. In contrast, the effect of inter-regional differences on overall differences has gradually reduced, while the effect of hypervariable density has steadily increased, becoming the most significant factor. High-quality development in China's animal industry exhibits a strong path dependency, with advancements typically occurring incrementally between adjacent levels and an insignificant probability of leapfrogging. The level of high-quality development in a given region is significantly influenced by the development levels observed in neighbouring regions, illustrating a phenomenon akin to the adage that One who is near vermilion is stained red, one who is near ink is stained black. Factors such as urbanisation rates, levels of scientific and technological innovation, transport infrastructure, levels of agricultural financial development, and population density all contribute positively to the high-quality development of China's animal industry. At the same time, a larger share of animal husbandry in both the overall industrial sector and the agricultural industry further contributes to this high-quality development; whereas, GDP per capita and fiscal support for agriculture do not appear to have a significant effect.